2004
DOI: 10.1038/sj.bjc.6601583
|View full text |Cite
|
Sign up to set email alerts
|

Forced expression of heat-shock protein 70 increases the secretion of Hsp70 and provides protection against tumour growth

Abstract: Although heat-shock protein 70 (Hsp70) has been considered an intracellular protein, we report that Hsp70 is secreted under normal cell culture conditions by human prostate cell lines, LAPC-4, PC-3, CWR-22, RWPE-1 and -2, LNCaP, and TRAMP (transgenic adenocarcinoma mouse prostate)-C2. We found that the secretion can be enhanced by transfection with cDNA encoding for Hsp70. To verify that the Hsp70 detected in the supernatant was not secondary to cell leakage, C2 cells were cotransfected with cytoplasmic Renill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Moreover, facilitation of surface localization or release of Hsp70 has been shown to correlate with increased immunogenicity of several tumor cell types tested in mice or at in vitro conditions [19,[47][48][49][50] These observations together with our findings indicate that Hsp70 overexpression in B16 cells could generate an excellent immune activating milieu through an elevated level of surface and released Hsp70. Furthermore, we showed that B16 melanoma cells chronically expressing excess Hsp70 lost their ability to release Hsp70 through active transport mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, facilitation of surface localization or release of Hsp70 has been shown to correlate with increased immunogenicity of several tumor cell types tested in mice or at in vitro conditions [19,[47][48][49][50] These observations together with our findings indicate that Hsp70 overexpression in B16 cells could generate an excellent immune activating milieu through an elevated level of surface and released Hsp70. Furthermore, we showed that B16 melanoma cells chronically expressing excess Hsp70 lost their ability to release Hsp70 through active transport mechanisms.…”
Section: Discussionsupporting
confidence: 67%
“…However, a recent proteomic analysis of human prostasomes revealed the presence of heat shock proteins in prostatic secretion (Utleg et al 2003). In addition, heat-shock protein 70 has been reported to be secreted from a variety of prostatic cell lines, and to show growth-inhibitory activity (Jones et al 2004, Wang et al 2004. Secreted mouse GRP78 may have a similar activity.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical vaccine models featuring surface HSP expression, whether driven by transfected genetic constructs (Zheng et al, 2001;Chen et al, 2002) or by the propensity of a given cell line to surface localize HSPs (Wang et al, 2004) were capable of generating antitumor immune responses. Other strategies used secretable chaperones and HSPs (again, artificially constructed or "naturally occurring" in certain tissue culture cells), successfully immunizing animals against tumor challenge (Yamazaki et al, 1999;X.…”
Section: Discussionmentioning
confidence: 99%